Estrogen receptor in hen oviduct chromatin, digested by micrococcal nuclease. - Massol, N (1978)
Nuclei from laying hen oviduct were prepared according to Hewish and Burgoyne i.e. in the presence of spermine and spermidine and in the absence of divalent cations and were then moderately digested by micrococcal nuclease. When the resulting chromatin was analysed by ultracentrifugation on a sucrose gradient, a peak of specific estradiol-binding sites was observed, sedimenting slightly faster (13-14 S) than the mononucleosomes (12 S). When the chromatin was centrifuged on a gradient containing heparin (5 microngram/ml) the sedimentation coefficient of the estradiol receptor peak shifted to 7-8 S; it returned to the 13-14 S position in the absence of heparin, when target organ chromatin was also present in the gradient. The preparation of the chromatin is described and the validity of the method to explore receptor localisation is discussed, as is the specificity of the receptor-DNA interaction.